Comparison of Magnetic Resonant Coupling Wireless Power Transfer Systems within Aligned and Unaligned Positions and Determining their Limits - Agcal, Ali; Bekiroglu, Nur; Ozcira, Selin (KOREAN MAGNETICS SOC, 2016)
In this study, the efficiencies for both the angular aligned and unaligned positions of the receiver and transmitter coils of wireless power transfer (WPT) systems are examined. Some parameters of the equivalent circuit were calculated with Maxwell 3D software. The analytical solution of the circuit was calculated in MATLAB program through the composition of the system's mathematical modeling. The numerical solution of the system, however, was calculated using PSIM, which is circuit simulation software. In addition, with the use of the finite element method (FEM) in Maxwell 3D software, transient analysis of the three-dimensional system was performed. The efficiency of the system was estimated through the calculation of input and output power. The results demonstrated that power was efficiently transmitted to a certain extent in aligned and unaligned positions. The results also revealed that, for aligned positions, high efficiency with air gaps of 15-20 cm can be obtained and that the efficiency quickly dropped with air gaps of more than 20 cm. For spatially unaligned positions, it was observed that wireless power transfer could be realized with high efficiency with air gaps of up to 10 cm and that efficiency quickly dropped with air gaps of more than 10 cm.
Keywords: wireless power transfer; magnetic resonant coupling; alignment of coils; system efficiency; Materials Science; Physics